Preparation method of graphene composite lithium iron phosphate positive electrode material

By gradually increasing the temperature and controlling the stirring conditions during the preparation process of graphene composite lithium iron phosphate cathode materials, the problem of large differences in length and diameter of different batches of products was solved, and the uniformity and electrochemical performance of the products were improved.

CN119340354APending Publication Date: 2025-01-21ZHONGKE LITHIUM BATTERY NEW ENERGY CO LTD

Patent Information

Application Number
CN202410373282.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing graphene composite lithium iron phosphate nanowire positive electrode materials have a large gap in length and diameter in different batches, which affects commercial large-scale production.

Method used

Optimize the preparation method of graphene composite lithium iron phosphate cathode material through gradually increasing temperature control, including stirring at 50-60°C, then gradually increasing the temperature to 90-99°C, and then at a lower temperature after a high-temperature water bath. Stir to reduce side reactions and particle agglomeration.

Benefits of technology

It achieves the stability of the product during the formation process, avoids structural damage and performance degradation caused by rapid temperature changes, improves the uniformity and electrochemical performance of the nanowires, and ensures the stability and uniformity of product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340354A_ABST
    Figure CN119340354A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a graphene composite lithium iron phosphate positive electrode material, and relates to the technical field of positive electrode materials, and the preparation method comprises the following steps: S1, adding a graphene oxide into deionized water, and stirring to obtain a solution I; s2, dissolving ferric salt in deionized water according to the mass ratio of the ferric salt to graphene oxide of 1: 0.05, adding the solution I, and stirring to obtain a solution II; s3, sequentially adding phosphoric acid, ethylene glycol and lithium salt into the solution II according to the molar ratio of ferric salt to phosphoric acid to lithium salt of 1: 1: 3, and stirring to obtain a solution III; s4, putting the solution III into a reactor, covering and sealing, heating in a gradient water bath, soaking a product obtained in the water bath with deionized water, and drying in a vacuum freeze dryer; s5, vacuum drying; the crystallinity and morphology of the product are optimized by accurately controlling the water bath temperature and time; and a uniform and ordered crystal structure is formed by staged water bath, so that the electrochemical performance of the product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a method for preparing a graphene composite lithium iron phosphate positive electrode material. Background Art

[0002] With the continuous consumption of traditional energy and the increasingly serious problem of environmental pollution, people's demand for new energy materials is becoming increasingly urgent. New energy sources such as solar energy, wind energy and tidal energy have been extensively developed and applied, but the discontinuous energy generated must be converted into continuous energy through energy storage devices in order to be used stably and continuously by people. This places high demands on the energy density and service life of energy storage devices. Lithium-ion batteries are considered to be the most promising energy storage batteries due to their high energy density, large capacity and long cycle life. They are widely used in electronic products, public transportation, national defense, military and aerospace. As an important component of lithium-ion batteries, positive electrode materials have an important influence on the electrochemical properties and safety performance of batteries. Lithium iron phosphate (LiFePO4) with olivine structure has attracted much attention due to its many advantages such as low cost, non-toxicity, high specific capacity, excellent cycle performance and long service life. Although LiFePO4 has many advantages that other positive electrode materials cannot match, its lower electronic conductivity and lower Li + The diffusion rate of LiFePO4 makes it difficult to apply it on a large scale. Currently, the main methods for modifying LiFePO4 include carbon coating, metal cation doping at the lithium and iron sites, preparation of nanoscale LiFePO4, and preparation of porous LiFePO4. Among them, carbon coating and preparation of nanoscale LiFePO4 can significantly improve the electrochemical performance of LiFePO4, and thus have attracted the attention of scientific researchers.

[0003] For example, the Chinese patent with announcement number CN106505201B discloses a graphene composite lithium iron phosphate nanowire positive electrode material and its preparation method, with a concentration of 2~4kg / m 3 The graphene oxide aqueous solution is designated as Solution I. Iron salt is dissolved in deionized water, added to Solution I, and stirred to obtain Solution II. Phosphoric acid, ethylene glycol, and lithium salt are then sequentially added to Solution II and stirred to obtain Solution III. Solution III is placed in a reactor, sealed with a lid, and the product obtained by water bathing at 80-90°C is soaked in deionized water for 1-2 hours, removed, and dried in a vacuum freeze dryer. The vacuum freeze-dried product is placed in a tubular atmosphere furnace, kept at 600-750°C under a protective atmosphere for 4-10 hours, and cooled with the furnace to obtain a graphene-composite lithium iron phosphate nanowire positive electrode material. This invention is characterized by easy operation, simple process, and suitability for industrial production. The resulting nanowires have controllable length and diameter, good dispersibility, and excellent electrochemical properties.

[0004] However, the length and diameter of products obtained from different batches vary greatly, which is not conducive to commercial-scale production. Summary of the Invention

[0005] The embodiment of the present application solves the agglomeration phenomenon of antibacterial and mildew-proof resin particles in the prior art by providing a method for preparing a graphene composite lithium iron phosphate positive electrode material, achieves better dispersion, and improves the antibacterial effect.

[0006] The present invention provides a method for preparing a graphene-composite lithium iron phosphate positive electrode material, which specifically comprises the following steps: S1. Add graphene oxide to deionized water and stir for 1-2 hours to obtain solution I, wherein the concentration of the graphene oxide aqueous solution is 4 kg / m 3 ; S2. Dissolve the iron salt in deionized water at a mass ratio of iron salt to graphene oxide of 1:0.05, add solution I, and stir for 5-8 minutes to obtain solution II; S3. According to the molar ratio of iron salt: phosphoric acid: lithium salt of 1:1:3, phosphoric acid, ethylene glycol, and lithium salt are added to solution II in sequence, and stirred to obtain solution III; S4. Place solution III in a reactor, seal it with a lid, heat it in a gradient water bath, and then soak the product obtained in the water bath in deionized water for 1-2 hours, take it out, and dry it in a vacuum freeze dryer for 48-72 hours; S5. Place the vacuum freeze-dried product in a tubular atmosphere furnace, raise the temperature to 600-650° C. under protective argon conditions, keep the temperature for 4-6 hours, and cool with the furnace to obtain a graphene composite lithium iron phosphate positive electrode material.

[0007] Furthermore, in step S2, the iron salt is ferrous sulfate heptahydrate.

[0008] Furthermore, in step S3, the lithium salt is lithium hydroxide monohydrate, and the stirring time is 1-3 hours.

[0009] Furthermore, in step S4, the gradient water bath heating is specifically as follows: first, heat the mixture in a water bath at 50-60° C. for 5-8 hours, then heat the mixture to 70-80° C. for 7-10 hours, and then heat the mixture to 90-99° C. for 10-12 hours.

[0010] Furthermore, in step S3, the amount of ethylene glycol added is 2-3% of the volume of solution III.

[0011] Furthermore, in step S3, the stirring temperature is 50-60° C., and the stirring time is 2-3 h.

[0012] Furthermore, in step S4, the gradient water bath heating is specifically as follows: first, heat the mixture in a water bath at 50-60° C. for 3-5 hours, then heat the mixture to 70-80° C. for 6-8 hours, and then heat the mixture to 90-99° C. for 8-10 hours.

[0013] Furthermore, in step S4, after the reaction in the sealed water bath is completed, the reactor is opened to continue the reaction.

[0014] Furthermore, the temperature of the reactor was lowered to 60-70°C after the reactor was no longer sealed.

[0015] Further, stirring is carried out at a temperature of 60-70° C. for 2-3 hours.

[0016] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages: First, gradually increasing the temperature can gradually stabilize the product during the formation process, avoiding product structure destruction or performance degradation caused by rapid temperature changes, and preventing particle agglomeration caused by excessively high initial temperatures. At lower temperatures, the particles are more dispersed and grow slowly. By gradually increasing the water bath temperature, the various components in the reaction system can be gradually activated, accelerating the growth rate and promoting the gradual progress of the reaction. At lower temperatures, slower reaction steps occur first, and as the temperature rises, faster reaction steps are triggered, thereby optimizing the entire reaction process. Staged water baths reduce the occurrence of side reactions. At lower temperatures, the conditions for the occurrence of side reactions are suppressed, and as the temperature gradually rises, the reaction system can gradually adapt and stabilize, reducing unnecessary side reactions. Second, at a temperature of 50-60°C, the solutes in the solution can be better dissolved and mixed, forming a uniform solution system, increasing the speed of subsequent reactions and reducing reaction time. Furthermore, the growth rate of the nanowires is moderate, allowing the nanowires to grow uniformly in the solution, avoiding unevenness caused by excessively fast or slow growth, and allowing the nanowires to form an orderly orientation and arrangement, prompting the nanowires to align in a specific direction, initially forming an ordered nanowire array. Third, after the high-temperature water bath, the reactor is no longer sealed and stirred at a lower temperature, which helps volatile impurities or unreacted products in the solution to escape, thereby improving the purity of the product; and during the stirring process, as the solvent gradually evaporates, the nanowires begin to solidify and connect with each other. The uniform evaporation of the solvent ensures that the nanowires maintain an orderly orientation and arrangement during the solidification process. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention is a flow chart of a method for preparing a graphene composite lithium iron phosphate positive electrode material. DETAILED DESCRIPTION

[0018] To facilitate understanding of the present invention, the present application will be described more comprehensively below with reference to the relevant drawings; the drawings show preferred embodiments of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described herein; on the contrary, the purpose of providing these embodiments is to enable a more thorough and comprehensive understanding of the disclosed content of the present invention.

[0019] It should be noted that the terms “vertical”, “horizontal”, “up”, “down”, “left”, “right” and similar expressions used in this document are for illustrative purposes only and do not represent the only implementation method.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention pertains; the terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items. Example 1

[0021] A method for preparing a graphene composite lithium iron phosphate positive electrode material, comprising the following specific steps: S1, the concentration of graphene oxide aqueous solution is 4kg / m 3 , add graphene oxide to deionized water and stir for 1-2 hours to obtain solution I; S2. Dissolve the iron salt in deionized water at a mass ratio of iron salt to graphene oxide of 1:0.05, add solution I, and stir for 5-8 minutes to obtain solution II; Wherein, the iron salt is ferrous sulfate heptahydrate; S3. According to the molar ratio of iron salt: phosphoric acid: lithium salt of 1:1:3, phosphoric acid, ethylene glycol, and lithium salt are added to solution II in sequence, and stirred for 1-3 hours to obtain solution III; the amount of ethylene glycol added is 2-3% of the volume of solution III; Wherein, the lithium salt is lithium hydroxide monohydrate; S4. Place solution III in a reactor, seal the reactor with a lid, and incubate in a water bath at 50-60°C for 5-8 hours. Then, heat the reactor to 70-80°C and incubate in a water bath for 7-10 hours. Then, heat the reactor to 90-99°C and incubate in a water bath for 10-12 hours. Soak the product obtained in the water bath in deionized water for 1-2 hours, remove the product, and dry it in a vacuum freeze dryer for 48-72 hours. S5. Place the vacuum freeze-dried product in a tubular atmosphere furnace, raise the temperature to 600-650° C. under protective argon conditions, keep the temperature for 4-6 hours, and cool with the furnace to obtain a graphene composite lithium iron phosphate positive electrode material.

[0022] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Gradually increasing the temperature can gradually stabilize the product during the formation process, avoiding product structure destruction or performance degradation caused by rapid temperature changes, and preventing particle agglomeration caused by excessively high initial temperatures. At lower temperatures, the particles are more dispersed and grow slowly. By gradually increasing the water bath temperature, the various components in the reaction system can be gradually activated, the growth rate can be accelerated, and the reaction can be gradually promoted. At lower temperatures, the slower reaction steps occur first, and as the temperature rises, the faster reaction steps are triggered, thereby optimizing the entire reaction process. Staged water baths reduce the occurrence of side reactions. At lower temperatures, the conditions for the occurrence of side reactions are suppressed, and as the temperature gradually rises, the reaction system can gradually adapt and stabilize, reducing unnecessary side reactions. By precisely controlling the water bath temperature and time, the crystallinity and morphology of the product are optimized; a uniform and ordered crystal structure is formed in stages, thereby improving the electrochemical performance of the product. The graphene composite lithium iron phosphate nanowires prepared in this embodiment have a length of 4-6 μm and a diameter of 330-390 nm. The obtained product has stable quality and high uniformity. Example 2

[0023] The above embodiment improves the uniformity of the product by increasing the temperature in stages, thereby further improving the initial extension of the nanowires.

[0024] S3. Add phosphoric acid, ethylene glycol, and lithium salt to solution II in the molar ratio of iron salt: phosphoric acid: lithium salt of 1:1:3, and stir for 2-3 hours at 50-60°C to obtain solution III. The amount of ethylene glycol added is 2-3% of the volume of solution III. S4. Place solution III in a reactor, seal the reactor with a lid, and incubate in a water bath at 50-60°C for 3-5 hours. Then, heat the reactor to 70-80°C and incubate in a water bath for 6-8 hours. Then, heat the reactor to 90-99°C and incubate in a water bath for 8-10 hours. Soak the product obtained in the water bath in deionized water for 1-2 hours, remove the product, and dry it in a vacuum freeze dryer for 48-72 hours. The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: At a temperature of 50-60°C, the solutes (iron salt, phosphoric acid and lithium salt) in the solution can be better dissolved and mixed to form a uniform solution system, thereby increasing the subsequent reaction speed and reducing the reaction time. At a stirring temperature of 50-60°C, the growth rate of the nanowires is moderate, so that the nanowires grow uniformly in the solution, avoiding the unevenness caused by too fast or too slow growth, so that the nanowires form an orderly orientation and arrangement, prompting the nanowires to be arranged in a specific direction, and initially forming an ordered nanowire array. Stirring at this temperature reduces the agglomeration and precipitation between the nanowires, maintains the dispersion of the nanowires in the solution, thereby forming an ordered and uniform nanowire structure. The graphene composite lithium iron phosphate nanowires prepared in this embodiment have a length of 4-6 μm and a diameter of 350-380 nm. Example 3

[0025] In the second embodiment, the temperature is increased during mixing and stirring to pre-react and improve the dispersion of the nanowires. This is further improved to further optimize the curing effect.

[0026] S4. Place Solution III in a reactor, seal it with a lid, and incubate it in a water bath at 50-60°C for 3-5 hours. Then, raise the temperature to 70-80°C and incubate it in a water bath for 6-8 hours. Then, raise the temperature to 90-99°C and incubate it in a water bath for 8-10 hours. Unseal the reactor, lower the temperature to 60-70°C, stir it for 2-3 hours, and then soak the product obtained in the water bath in deionized water for 1-2 hours. Remove it and dry it in a vacuum freeze dryer for 48-72 hours. The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: After the high-temperature water bath, the reactor is no longer sealed and stirred at a lower temperature, which helps the volatile impurities or unreacted products in the solution to escape, thereby improving the purity of the product; the subsequent deionized water immersion process can further remove ions or impurities adsorbed on the surface of the nanowires, ensuring the cleanliness of the product. During the stirring process, as the solvent gradually evaporates, the nanowires begin to solidify and connect with each other. The uniform evaporation of the solvent ensures that the nanowires maintain an orderly orientation and arrangement during the solidification process. The graphene composite lithium iron phosphate nanowires prepared in this embodiment have a length of 5-6 μm and a diameter of 360-380 nm.

[0027] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations are possible, such as adding a base fabric to the membrane to enhance durability. Any modifications, equivalent substitutions, or improvements within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A method for preparing a graphene composite lithium iron phosphate positive electrode material, characterized in that: The specific steps include: S1. Add graphene oxide to deionized water and stir for 1-2 hours to obtain solution I, wherein the concentration of the graphene oxide aqueous solution is 4 kg / m 3 ; S2. Dissolve the iron salt in deionized water at a mass ratio of iron salt to graphene oxide of 1:0.05, add solution I, and stir for 5-8 minutes to obtain solution II; S3, according to the molar ratio of iron salt: phosphoric acid: lithium salt being 1:1:3, phosphoric acid, ethylene glycol and lithium salt are added to solution II in sequence, and stirred to obtain solution III; S4, placing solution III in a reactor, sealing it with a cover, heating it in a gradient water bath, and then soaking the product obtained in the water bath in deionized water for 1-2 hours, taking it out, and drying it in a vacuum freeze dryer for 48-72 hours; S5. Place the vacuum freeze-dried product in a tubular atmosphere furnace, raise the temperature to 600-650° C. under protective argon conditions, keep the temperature for 4-6 hours, and cool with the furnace to obtain a graphene composite lithium iron phosphate positive electrode material.

2. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S2, the iron salt is ferrous sulfate heptahydrate.

3. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S3, the lithium salt is lithium hydroxide monohydrate, and the stirring time is 1-3 hours.

4. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S4, the gradient water bath heating is specifically as follows: firstly, water bath at 50-60°C for 5-8h, then heating to 70-80°C for 7-10h, and then heating to 90-99°C for 10-12h.

5. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S3, the amount of ethylene glycol added is 2-3% of the volume of solution III.

6. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 5, characterized in that: In step S3, the stirring temperature is 50-60°C and the stirring time is 2-3h.

7. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 6, characterized in that: In step S4, the gradient water bath heating is specifically as follows: firstly, water bath at 50-60°C for 3-5h, then heating to 70-80°C for 6-8h, and then heating to 90-99°C for 8-10h.

8. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 7, characterized in that: In step S4, after the reaction in the sealed water bath is completed, the lid is opened to continue the reaction.

9. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 8, characterized in that: The temperature dropped to 60-70°C after the reactor was no longer sealed.

10. The method for preparing a graphene composite lithium iron phosphate positive electrode material according to claim 9, characterized in that: Stir at 60-70°C for 2-3h.

Citation Information

Patent Citations

  • Graphene-composite lithium iron phosphate nanowire cathode material and its preparation method

    CN106505201B

Cited By

  • Lithium iron phosphate positive electrode material and preparation method thereof

    CN120004236A

  • Lithium iron phosphate cathode material and its preparation method

    CN120004236B